PENGAMANAN DATA DALAM JARINGAN LAN DENGAN MENGGUNAKAN ALGORITMA CHIPER TRANSPOSISI - Simanullang, Sanco (Universitas Methodist Indonesia, 2019)
Data security is important in the implementation of information technology, especially in the field of computers, which allows thousands of people and computers around the world to be connected in a virtual world known as cyberspace or the internet. This can create new challenges and demands for the availability of a data security system that is as sophisticated as the advances in computer technology itself. In cryptography, data sent over the network will be disguised in such a way that even if the data can be read by third parties, it should not be understood by unauthorized parties. Data to be sent and has not been encrypted which produces ChipperTtext. The implementation of the transposition algorithm for securing data flowing in the Local Area Network (LAN), the transposition process changes the arrangement of letters from the source text (plaintext), with a column transposition cipher, to obtain the words in a barred manner. In the transposition cipher, the plaintext is the same, but the sequence is changed. . This algorithm transposes a series of characters in the text. Another name for this method is permutation because transpose each character in the text is the same as permutating the characters so that this application generates encrypted data on the network stream and returns it to plaintext at the final destination. So that it can be ensured that the information and data sent to other parties are safe from unauthorized parties.